1984
DOI: 10.1099/0022-1317-65-2-355
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Morphology and Antigenic Characterization of Measles Virus Envelope Components

Abstract: SUMMARYMeasles virus haemagglutinin (H), fusion (F) and matrix (M) components were purified by affinity chromatography using monoclonal antibodies coupled to CNBractivated Sepharose. H and M proteins were purified to homogeneity as determined by polyacrylamide gel electrophoresis by a single cycle of adsorption-desorption. The corresponding purification of the F protein required two cycles of adsorptiondesorption. After the second adsorption an extra wash with 1 M-guanidine-HCl was employed to remove the conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…IAC purification of the F protein was carried out as previously described with minor modifications (Varsanyi et al, 1984;De Vries et al, 1987). Briefly, 2~ Triton X-100 was used to solubilize the membrane proteins of the concentrated virus suspension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IAC purification of the F protein was carried out as previously described with minor modifications (Varsanyi et al, 1984;De Vries et al, 1987). Briefly, 2~ Triton X-100 was used to solubilize the membrane proteins of the concentrated virus suspension.…”
Section: Methodsmentioning
confidence: 99%
“…1), corresponding to the F~ component and the disulphide-linked F1-F2 complex of the F protein respectively (Hardwick & Bussell, 1978;Varsanyi et al, 1984). The protein observed at Mr l 10000 in the gel under non-reducing conditions is probably a dimer of the 55 000 Mr F protein, since it also reacted with monoclonal antibody F17-21 in a Western blotting experiment (not shown).…”
Section: Purification and Incorporation Of The F Protein Into Iscomsmentioning
confidence: 99%
“…It was also shown that the purified H glycoprotein can be stored for several days at -70 °C after lyophilization, and its biological activity (haemagglutination) and recognition by an anti-H monoclonal antibody specific for a conformational determinant can be fully conserved provided that H glycoprotein is associated with artificial membranes. The purification of measles H glycoprotein has been reported previously using lectin affinity in conjunction with gel filtration (Christie et al, 1981 ;Lund & Salmi, 1981) or immunoaffinity (Bellini et al, 1981;Varsanyi et al, 1984) chromatography. These techniques required the desorption of the material using high salt (3 M-KSCN), 8 M-urea, 1% sodium deoxycholate or low pH (0.2 M-glycine pH 3.0) solutions, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to H inhibit haemagglutination by the virus and adsorption to host cells, and antibodies to F inhibit haemolysis and membrane fusion (Varsanyi et al, 1984;Merz et al, 1980). The importance of anti-F antibodies in vivo is highlighted by the development of atypical measles in recipients of a formalin-inactivated virus in whom no anti-F antibodies could be demonstrated (Norrby et al, 1975).…”
Section: Introductionmentioning
confidence: 99%